Regulation of cAMP Intracellular Levels in Human Platelets Stimulated by 2‐Arachidonoylglycerol. Issue 5 (18th October 2015) - Signorello, Maria Grazia; Leoncini, Giuliana
ABSTRACT: We demonstrated that in human platelets the endocannabinoid 2‐arachidonoylglycerol (2‐AG) decreased dose‐ and time‐dependently cAMP intracellular levels. No effect on cAMP decrease induced by 2‐AG was observed in the presence of the adenylate cyclase inhibitor SQ22536 as well in platelets pretreated with the thromboxane A2 receptor antagonist, SQ29548 or with aspirin, inhibitor of arachidonic acid metabolism through the cyclooxygenase pathway. An almost complete recovering of cAMP level was measured in platelets pretreated with the specific inhibitor of phosphodiesterase (PDE) 3A, milrinone. In platelets pretreated with LY294002 or MK2206, inhibitors of PI3K/AKT pathway, and with U73122, inhibitor of phospholipase C pathway, only a partial prevention was shown. cAMP intracellular level depends on synthesis by adenylate cyclase and hydrolysis by PDEs. In 2‐AG‐stimulated platelets adenylate cyclase activity seems to be unchanged. In contrast PDEs appear to be involved. In particular PDE3A was specifically activated, as milrinone reversed cAMP reduction by 2‐AG. 2‐AG enhanced PDE3A activity through its phosphorylation. The PI3K/AKT pathway and PKC participate to this PDE3A phosphorylation/activation mechanism as it was greatly inhibited by platelet pretreatment with LY294002, MK2206, U73122, or the PKC specific inhibitor GF109203X. Taken together these data suggest that 2‐AG potentiates its power of platelet agonist reducing cAMP intracellular level. J. Cell. Biochem. 117: 1240–1249, 2016. © 2015 Wiley Periodicals, Inc.